Is bleeding on probing a differential diagnosis between periimplant health and disease? - Priscila Ladeira Casado; Ricardo Villas-Bôas; Luana Cristine Leão da Silva; Letícia Ladeira Bonato; José Mauro Granjeiro (Universidade Estadual de Campinas, 2015)
As far as the periimplant anatomy is considered, the question raised is whether or not healthy periimplant tissues present bleeding on probing (BOP). Aim: To assess if the criterion BOP is strictly related to periimplant disease (PID). Methods: 134 patients were included in this study. All periimplant regions were clinically and radiographically evaluated. Patients were assigned to 3 groups based on radiographic and clinical aspects in the periimplant region: Group A (healthysites) - no signs of mucosal inflammation or bone loss; Group B (mucositis) - red and swollen mucosa, but no radiographic bone loss; Group C (periimplantitis) - radiographically confirmed pathological bone loss. After this classification, all periimplant sulci were probed at 4 sites (mesial, distal, buccal, lingual/palatal). Patients' mean age was 51.7±12.4 years, 77 women and 57 men, with a total of 486 osseointegrated endosseous implants. Results: Groups A and C showed significant difference in age and implant region distribution (p=0.009 and p=0.008, respectively). After initial clinical and radiographic diagnosis of periimplant status, 33 (20.1%) regions showed BOP in group A. All regions in Group B presented BOP. In Group C, 41 (19.9%) regions showed no BOP. All groups differed significantly considering BOP as diagnosis parameter (p<0.0001). Conclusions: BOP was always present in inflamed mucosa, but it was not always absent in healthy mucosa. Not all periimplantitis regions showed BOP. Clinical and radiographic aspects must always be considered together for diagnosis of PID, even if BOP is absent.